PENGARUH MOTIVASI KERJA ISLAM DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA PT. ASURANSI BRI LIFE DI KOTA MAKASSAR (Fakultas Dakwah dan Komunikasi, 2021)
The results showed that the implementation of the dakwah management function at the Head Office of Paccinongang, Gowa Regency includes the planning of the Takhthith da'wah) which includes long-term planning and short-term planning, organizing da'wah (Tanzhim) includes work specialization and departmentalization, propagation of da'wah (Tawjih) including giving motivation, guidance, and guidance and establish relationships, and control and evaluate dakwah (Riqabah) including direct and indirect control. Opportunities are opportunities used to obtain these benefits. Given the opportunity, the implementation of the dakwah management function at the Lurang Paccinongang Office of Gowa Regency can improve the performance of competent employees including work discipline and the creation of cooperation. Meanwhile, the challenge is a process that hinders the running of activity, including differences in perceptions and lack of office facilities